Destinasi Taman Wisata Alam Gunung Tampomas: - Hardy, Willia Yusup; Setianti, Yanti; Dida, Susanne (JURNAL DESTINASI PARIWISATA, 2021)
Sumedang Regency at West Java Indonesia has a lot of tourism potential. One of them is the potential for ecotourism in the Mount Tampomas natural tourism park. Mount Tampomas Nature Park is a tourist area in Sumedang Regency that has not been developed optimally. Mount Tampomas Nature Park has the potential for natural beauty, biotic potential, potential for springs and potential for hot springs. In developing the tourism potential, it will have an impact on the economic, tourism, cultural, social education and conservation sectors for the lives of the surrounding community. So that the potential development of Mount Tampomas needs to be developed properly because it has a major effect on increasing tourism branding in Sumedang Regency. This study is to determine the development and management of the tourist destination branding of Mount Tampomas Nature Tourism Park as an ecotourism area. The method used in this research is descriptive qualitative research method, with data collection techniques literature studies. This descriptive research method is used to find an overview of the branding activities of the Mount Tampomas Nature Tourism Park, by knowing tourist satisfaction and support from the local community for the progress of ecotourism development in the Mount Tampomas natural tourism park. So the researchers used the SWOT analysis technique to determine the supporting and inhibiting factors in the development of ecotourism in the Mount Tampomas natural tourism park. Keywords: Branding, Tourism, Destinations